Industrial Training Report: Siti Hasmah Digital Library Multimedia University Melaka / Muhammad Shafiq Amirullah - Amirullah, Muhammad Shafiq (Faculty of Information Management, 2019)
Industrial training is one of the compulsory study requirements in order to fulfil the needs of final year students of IM244 to complete a degree. In order to accomplish the industrial training requirement, students must undergo at least five (5) months of training at the organization which approved by the faculty months before the training begins. Related to course that have been taken, students should choose organization that is related and offers job scopes which consist of library management fields. Therefore, I have decided to choose Siti Hasmah Digital Library (SHDL}, Multimedia University Melaka to complete my training which begins from 1st August until 31st December 2019, and the duties rotated through all departments available. The report basically consist four (4) chapter which are about introduction of the organization, organization information, industrial training activities throughout the training period and industrial training reflections.